Faktor-Faktor Yang Mempengaruhi Adanya Limbah Pada Pekerjaan Konstruksi Pada Pembangunan Mal Pelayanan Publik Gowa - Pakondo, Seriyanti Tasin; Abduh, M. Natsir; Yunus, Ahmad Yauri (Jurnal Penelitian Teknik Sipil Konsolidasi, 2025)
Construction waste is often considered non-hazardous and not a major environmental concern. However, in reality, it can significantly contribute to environmental degradation, particularly during construction, renovation, and demolition activities. This study aims to identify the factors contributing to waste generation in the construction of the Gowa Public Service Mall. Key factors analyzed include Design, Handling, Workers, Construction Management, Material Waste Management, and Procurement/Purchasing. The study employs a quantitative approach using SPSS for analysis, with a sample size of 30 participants. Based on the percentage analysis, the study found that the design factor (X1) had a mean value of 2.71, handling (X2) scored 2.90, workers (X3) scored 2.57, construction management scored 2.85, material waste management (X5) had the highest mean at 2.98, and procurement (X6) scored 2.67. Among these, material management was identified as the most significant factor contributing to waste in the Gowa Public Service Mall construction, with a mean score of 2.98.